Role of self help groups in women empowerment and health - B.C., Narasimha; P., Anand; K. S., Ravish; S. S., Navya; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2017)
Background: Self-help groups (SHGs) are small voluntary association of people from the same socio-economic background with a purpose of solving their common problems through self-help and mutual help. Since Women empowerment and health are interrelated -women’s empowerment cannot be achieved by ignoring issues related to health of women. There have been fewer attempts to address the issue of women’s health so as to have an impact on their total wellbeing. Hence the present study intends to explore the extent to which self-help groups are involved in health and also identify other possible methods to increase their involvement in health related matters. Methods: A Community based cross sectional study was conducted in urban field practice area of Bangalore Medical College and Research Institute. Banglore, India. 95 women who were involved in SHG for 1 year were interviewed by a pre- validated questionnaire. Results: Out of 98 women 95 were interviewed, 62.1% were literates, 65.26% received economic help through this programme, 26.3% got importance in family as well as community, 21% had improvement in personal health, 68.4% of individuals self decides to seek medical care for health related issues. Conclusions: Self-help group is a useful platform to enhance women’s health through increased knowledge and awareness on health issues, and financial security during health emergencies etc. it’s very active in providing income generating activities. However there is no much significant improvement in health behaviour or knowledge about health related issues.